Synergistic anti-tumor effects of melatonin and PUFAs from walnuts in a murine mammary adenocarcinoma model - Garcia, Carolina Paola (2014)
Objective The aim of this study was to determine the effects of some polyunsaturated fatty acids plus phytomelatonin from walnuts in the development of mammary gland adenocarcinoma. Methods BALB/c mice were fed a semisynthetic diet supplemented with either 6% walnut oil and 8% walnut flour containing phytomelatonin (walnut diet: WD); or 6% corn oil plus commercial melatonin (melatonin diet: MD), or the control group (CD), which received only 6% of corn oil. Membrane fatty acids of tumor cells (TCs) were analyzed by gas liquid chromatography, cyclooxygenase (COX) and lipoxygenase (LOX) derivatives, and plasma melatonin by high-performance liquid chromatography; apoptosis and tumor-infiltrating lymphocytes by flow cytometry. Results TCs from the MD and WD mice showed significant decreases in linoleic acid compared with the CD group (P < 0.05). Significantly lower levels of LOX-[13(S)-HODE] were found in TCs from the MD and WD group than in CD (P < 0.0001). COX-[12(S)-HHT] was lower and 12 LOX-[12(S)-HETE] was higher in TCs from the MD group than form the WD and CD arms (P < 0.05). Plasma melatonin, apoptosis, tumor infiltration, and survival time were significantly lower in CD mice than in MD and WD mice (P < 0.05). Conclusions This study shows that melatonin, along with polyunsaturated fatty acids, exerts a selective inhibition of some COX and LOX activities and has a synergistic anti-tumor effect on a mammary gland adenocarcinoma model.